A spanyol integralista és „mesztic” katolikusok vitájáról 1884-1887 - Semsey, Viktória (Acta Scientiarum Socialium, 2012)
The discussion between the Spanish integralist and „Mestizos” Catholics in 1884–1887: the briefly sketched picture shows how the fragmentation within the Spanish Catholic Church were embedded in the Spanish political and social life in the second half of the 19th century, and what was the relationship with the papal policy. The author chose Felix SardÃ y Salvany’s „Liberalism is a sin” and Pazos de Celestino’s „Procedure against the integralism” as a source of his works.